2020
DOI: 10.3389/fimmu.2020.601497
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Nanomedicines: A Revolution of Tumor Immunotherapy

Abstract: Immunotherapies have been accelerating the development of anti-cancer clinical treatment, but its low objective responses and severe off-target immune-related adverse events (irAEs) limit the range of application. Strategies to remove these obstacles primarily focus on the combination of different therapies and the exploitation of new immunotherapeutic agents. Nanomedicine potentiates the effects of activating immune cells selectively and reversing tumor induced immune deficiency microenvironment through multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 134 publications
(143 reference statements)
0
21
0
Order By: Relevance
“…In general, although immune cells within the body are capable of recognizing and killing tumor cells, anti-tumor immune responses in the TME are suppressed due to direct or indirect tumor interference with, and/or inhibition of, functions of tumor-antagonizing immune cells acting via many mechanisms. Ultimately, dysfunctional immunoregulation within the TME promotes proliferation and differentiation of tumor-promoting immune cells that eventually lead to abnormal immunosurveillance and tumor cell immune escape ( Li W. et al, 2020 ; Lei et al, 2020 ; Liskova et al, 2020 ). Several active components of ginseng may exert anti-tumor effects by interfering with the differentiation and maturation of tumor-promoting immune cells, leading to reversal of the inhibitory phenotype of tumor-antagonizing immune cells and restoration of anti-tumor functions of innate ( Table 2 ) and acquired immune cells.…”
Section: Ginseng May Regulate the Tumor Immunosuppressive Microenvironmentmentioning
confidence: 99%
“…In general, although immune cells within the body are capable of recognizing and killing tumor cells, anti-tumor immune responses in the TME are suppressed due to direct or indirect tumor interference with, and/or inhibition of, functions of tumor-antagonizing immune cells acting via many mechanisms. Ultimately, dysfunctional immunoregulation within the TME promotes proliferation and differentiation of tumor-promoting immune cells that eventually lead to abnormal immunosurveillance and tumor cell immune escape ( Li W. et al, 2020 ; Lei et al, 2020 ; Liskova et al, 2020 ). Several active components of ginseng may exert anti-tumor effects by interfering with the differentiation and maturation of tumor-promoting immune cells, leading to reversal of the inhibitory phenotype of tumor-antagonizing immune cells and restoration of anti-tumor functions of innate ( Table 2 ) and acquired immune cells.…”
Section: Ginseng May Regulate the Tumor Immunosuppressive Microenvironmentmentioning
confidence: 99%
“…US-mediated immunogenic manifestations have broadened the immunotherapeutic outcomes. Immunotherapy coupled with nanomedicine triggered under ultrasound has become a primary antitumor therapy, 250 establishing an accurate, adjustable, and controlled system of safe immunotherapy. Biologically, US combined with with NPs activates proinflammatory responses, antigen presentation, and infiltration of activated leukocytes in the TME by reducing immunosuppressor molecules and reducing the hypoxic environment.…”
Section: Enhancing Cancer Immunotherapeutic Efficacy By Integrating N...mentioning
confidence: 99%
“…To investigate the feasibility of FEGCG/Zn as an effective delivery platform, the nanoassemblies‐forming features were evaluated in chemical drugs (sorafenib [Sor], gemcitabine [Gem], and doxorubicin [DOX]), nucleic acids (small interfering RNA [siRNA]), peptides (melittin [MPI]), and proteins (bovine serum albumin [BSA]) by parameters including drug loading, stability, cargo release, and cytosolic delivery efficiency ( Figure 1 a ). Considering well‐documented efficacy of PD‐L1‐based immunotherapy and prolonged circulation time with erythrocyte‐based drug delivery, [ 17 ] siPD‐L1 and erythrocytes were selected to validate the potency of the fabricated biomimetic delivery system. Our results showed that not only the erythrocytes part of the system could improve the tumor accumulation of siPD‐L1, but also the released FEGCG/Zn and siPD‐L1 could alleviate T cells exhaustion by blocking PD‐1/PD‐L1 engagement, resulting in the enhanced efficacy of anti‐PD‐L1 immunotherapy (Figure 1b‐c ).…”
Section: Introductionmentioning
confidence: 99%